The Relationship between Innovation and Economic Growth: Evidence from Chile and Mexico - Zayas-Marquez, Carolina; Ávila López, Luis Alfredo (RAN - Revista Academia & Negocios, 2022)
Purpose: This paper analyzes the causal relationship between innovation and long-term per capita economic growth in Chile and Mexico for the period 1996-2015. Design/methodology: This study uses six innovation indicators, were assessed using Granger`s test of causality: number of patents filed by resident and non-residents, spending on research and development (R&D), R&D activities, high tech exports and scientific and technical articles. Results: The study found evidence of one-way and two-way causality between innovation and per capita economic growth. Both countries face the challenge of improving the environment to attract enough FDI (foreign direct investment). Implications: Latin America is a diverse region. According to the 2017 Global Innovation Index, Chile ranked nº 46 while Mexico ranked nº 58, the two countries generally ranked as the most innovative in Latin America. Originality/value: It is important to note that all these innovation indicators are strongly related to per capita economic growth. Limitations / Implications: Politicians and academics interested in this topic should know that the two-way relationship between innovation and per capita economic growth does not necessarily reflect the whole situation. Practical implications: More variables such as education and policy continuity should be studied to improve estimates.